2022
DOI: 10.1200/jco.2022.40.16_suppl.3552
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes of biosimilar bevacizumab-awwb versus reference bevacizumab in patients with metastatic colorectal cancer.

Abstract: 3552 Background: Bevacizumab-awwb was the first biosimilar approved by the U.S. Food and Drug Administration (FDA) for treatment of cancer and became available for use in July 2019. Clinical comparative efficacy and safety of bevacizumab-awwb to bevacizumab was established in a single study of adult patients with advanced non-squamous non-small cell lung cancer. Approval based on extrapolation was granted by the FDA for all other indications, including metastatic colorectal cancer (mCRC). The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…12,34 Our results were also consistent with data from a most recent retrospective, non-inferiority cohort study of patients with mCRC in the United States that compared treatment outcomes of naïve patients initiating bevacizumab-awwb (n = 239) versus historical control group of naïve patients initiating RP (n = 1,206), which showed that one-year OS with bevacizumab-awwb (72.8%) was non-inferior to that with RP (73.1%). 35 EOIs reported in naïve patients and switchers during bevacizumab-awwb-containing treatment were also generally consistent with previously published data for mCRC patients treated with 1L RP [6][7][8][11][12][13]35 and consistent with adverse reactions described in bevacizumab-awwb labeling. 24 The aforementioned non-inferiority cohort study in mCRC patients confirmed that no significant differences in serious adverse events were detected between bevacizumabawwb and RP treatment groups.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…12,34 Our results were also consistent with data from a most recent retrospective, non-inferiority cohort study of patients with mCRC in the United States that compared treatment outcomes of naïve patients initiating bevacizumab-awwb (n = 239) versus historical control group of naïve patients initiating RP (n = 1,206), which showed that one-year OS with bevacizumab-awwb (72.8%) was non-inferior to that with RP (73.1%). 35 EOIs reported in naïve patients and switchers during bevacizumab-awwb-containing treatment were also generally consistent with previously published data for mCRC patients treated with 1L RP [6][7][8][11][12][13]35 and consistent with adverse reactions described in bevacizumab-awwb labeling. 24 The aforementioned non-inferiority cohort study in mCRC patients confirmed that no significant differences in serious adverse events were detected between bevacizumabawwb and RP treatment groups.…”
Section: Discussionsupporting
confidence: 88%
“…Bevacizumab-awwb appeared to be well tolerated in both naïve patients and switchers, with observed EOIs as expected and similar to those of RP. [6][7][8][11][12][13]35 Effectiveness outcomes with bevacizumab-awwb in naïve patients were generally consistent with those reported in previously published real-world studies of 1L RP in patients with mCRC. 11,12,[34][35][36] In two US registry studies (ARIES and BRiTE), median PFS of ~10 months and median OS of ~23 months were reported in mCRC patients who had a median duration of 5 months of 1L RP use.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations